1981
DOI: 10.1152/jappl.1981.51.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carotid body denervation on arousal response to hypoxia in sleeping dogs

Abstract: We studied the arousal and ventilatory responses to hypoxia during sleep in three trained dogs, before and 1-4 wk after carotid body denervation (CBD). During the studies the dogs breathed through a cuffed endotracheal tube inserted via a chronic tracheostomy. Eucapnic progressive hypoxia was induced by a rebreathing technique, and arterial O2 saturation (Sao2) was measured with an ear oximeter. Sleep stage was determined by electroencephalographic and behavioral criteria. Following CBD, all dogs exhibited hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
53
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(59 citation statements)
references
References 0 publications
6
53
0
Order By: Relevance
“…In support of this, Bowes et a/. have reported that bilateral vagal blockade delays the arousal response to rapidly developing hypoxemia in adult dogs (18). The third possibility is that arterial hypoxemia stimulates the carotid bodies, which produces an increase in heart rate and blood pressure and stimulates the carotid sinus baroreceptors, which causes arousal.…”
Section: Discussionmentioning
confidence: 90%
“…In support of this, Bowes et a/. have reported that bilateral vagal blockade delays the arousal response to rapidly developing hypoxemia in adult dogs (18). The third possibility is that arterial hypoxemia stimulates the carotid bodies, which produces an increase in heart rate and blood pressure and stimulates the carotid sinus baroreceptors, which causes arousal.…”
Section: Discussionmentioning
confidence: 90%
“…First, arousal is required for termination of apneic spells in adults with obstructive sleep apnea (13). Activity of the carotid bodies is required for arousal in adult dogs (20) and newborn lambs (2 1) subjected to progressive hypoxia. Thus, carotid body inactivity could well lead to failure of arousal and to apneas becoming prolonged and more likely to be associated with hypoxia and bradycardia.…”
Section: Discussionmentioning
confidence: 99%
“…In OSA, arousals are triggered by inspiratory effort against the occluded airway, 29 hypoxia, 30 and hypercapnia. 31 The stimuli for arousals following central apneas are not as well understood.…”
Section: Discussionmentioning
confidence: 99%